Tunable passively Q-switched ultranarrow linewidth erbium-doped fiber laser - Zulkifli, M. Z.; Muhammad, Farah Diana; Mohd Azri, M. F.; Mohd Yusof, M. Khairi; Hamdan, K. Z.; Samsudin, Sani A.; Yasin, M. (Elsevier BV, 2020)
A tunable passively Q-switched erbium-doped fiber laser with ultranarrow linewidth is proposed and demonstrated. With the single wall carbon nanotubes (SWCNTs) as the passive Q-switch, the ultranarrow linewidth laser operation is realized based on spectral filtering effect. Using an ultranarrow tunable bandpass filter (UNTBF). The Q-switched laser spectrum is tunable from 1525 to 1561 nm, covering a wavelength range of 36 nm. At 1545 nm, the highest repetition rate of ~38 kHz and the lowest pulse width of 1.15 μs are obtained, with the corresponding pulse energy of approximately 0.18 nJ. The linewidth measurement using self-heterodyne technique yields a linewidth value of 17.5 kHz, which may be the narrowest linewidth for a Q-switched fiber laser to the best of our knowledge.